2020
DOI: 10.1186/s12967-020-02323-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an autophagy-related gene expression signature for prognosis prediction in prostate cancer patients

Abstract: Background: Prostate cancer (PCa) is one of the most prevalent cancers that occur in men worldwide. Autophagyrelated genes (ARGs) may play an essential role in multiple biological processes of prostate cancer. However, ARGs expression signature has rarely been used to investigate the association between autophagy and prognosis in PCa. This study aimed to identify and assess prognostic ARGs signature to predict overall survival (OS) and disease-free survival (DFS) in PCa patients. Methods: First, a total of 234… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 29 publications
(29 reference statements)
4
69
0
Order By: Relevance
“…Jia et al demonstrated that overexpression of MAFG-AS1 lncRNA primarily downregulated miR-339-5p levels in non-small-cell carcinoma cells, and MMP15 is a miR-339-5p target [40] . In addition, Hu et al illustrated that MAP2K7 might be a promising prognostic molecular biomarker in PCa [41] . Nevertheless, the role of hsa-miR-6825-5p in PCa development has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Jia et al demonstrated that overexpression of MAFG-AS1 lncRNA primarily downregulated miR-339-5p levels in non-small-cell carcinoma cells, and MMP15 is a miR-339-5p target [40] . In addition, Hu et al illustrated that MAP2K7 might be a promising prognostic molecular biomarker in PCa [41] . Nevertheless, the role of hsa-miR-6825-5p in PCa development has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The Wilcoxon signed-rank test in package "limma" in R software (version 3.6.3) was applied to screen the differentially expressed ARGs between HCC and normal tissues, with the criteria of |log 2 fold change (FC)|>1.5 and adjusted P-value < 0.05 [16,18]. Then, we combined the expression data of the differentially expressed ARGs with the corresponding clinical data.…”
Section: Differentially Expressed Args In Hccmentioning
confidence: 99%
“…Then, we combined the expression data of the differentially expressed ARGs with the corresponding clinical data. Univariate Cox regression and multivariate Cox regression analyses were applied to pick out the ARGs that were closely related to OS in HCC [18]. We also performed the Lasso regression to remove ARGs that might be closely correlated with others [14,16].…”
Section: Differentially Expressed Args In Hccmentioning
confidence: 99%
“…Kaplan-Meier method was applied to evaluate the differences in high-risk and low-risk groups in term of the predictive signature. Besides, the accuracy of prognostic prediction model was determined by the ROC curve in package "survivalROC" in R software [21].…”
Section: Validation the Prognostic Modelmentioning
confidence: 99%
“…To investigate the molecular mechanisms of autophagy-associated genes in GC, GO and KEGG enrichment analyses were carried out and visualized by R software with "ggplot2", "GO plot", "DOSE", and "Cluster Pro ler" packages, etc [21]. The p-value < 0.05 and q-value < 0.05 were set as the criteria.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%